2013
DOI: 10.4238/2013.february.28.19
|View full text |Cite
|
Sign up to set email alerts
|

Increased androgen receptor messenger RNA in frontal-parietal hair follicles of women with androgenetic alopecia

Abstract: ABSTRACT. Normal testosterone levels are frequently observed in women with androgenetic alopecia (AGA), suggesting the involvement of androgen sensitivity in this condition. Androgen sensitivity is related to androgen receptor (AR) messenger RNA (mRNA) production in hair follicles and is negatively related to the number of CAG repeats present in exon 1 of the AR gene. The aim of this study was to compare AR expression in AGA women with normal controls and to correlate this expression with the number of CAG rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Normal testosterone levels are frequently observed in women with androgenetic alopecia (AGA), suggesting the involvement of androgen sensitivity in this condition. It was recently reported the increased AR messenger RNA expression in frontal-parietal hair follicles of women with AGA compared to controls [121] confirming the relation between androgen sensitivity and the AR mRNA production. Moreover, AR content in female frontal hair follicles is approximately 40% lower than in male counterparts.…”
Section: Accepted Manuscriptmentioning
confidence: 60%
“…Normal testosterone levels are frequently observed in women with androgenetic alopecia (AGA), suggesting the involvement of androgen sensitivity in this condition. It was recently reported the increased AR messenger RNA expression in frontal-parietal hair follicles of women with AGA compared to controls [121] confirming the relation between androgen sensitivity and the AR mRNA production. Moreover, AR content in female frontal hair follicles is approximately 40% lower than in male counterparts.…”
Section: Accepted Manuscriptmentioning
confidence: 60%
“…Dermal papilla cells from androgen dependent regions, contain higher levels of androgen receptors (AR) than those from androgen-insensitive areas 25 . Also, in women with androgenetic alopecia, increased AR expression in the FP region has been found (not observed in normal controls), proving the role of androgen hypersensitivity in this region 26 . Moreover, a second estrogen receptor, estrogen receptor β (ER β), present in androgen target tissues, as the prostate, has been also, identified in both male and female non balding human scalp skin 24 .…”
Section: Discussionmentioning
confidence: 89%
“…Richeti et al [26] showed that the level of mRNA in the AR at the frontal-parietal region in women with AGA was higher than the occipital region, and a significant negative correlation was observed between the amount of AR mRNA and the mean number of CAG repeats despite no significant difference in the control group. The study also indicated no significant difference in the CAG repeats between patients and controls, and suggested that the difference in expression of the AR gene could be attributed to the level of mRNA.…”
Section: Discussionmentioning
confidence: 99%